(untitled) (Journal of Business and Management Research, 2022)
Researchers have been trying to understand and establish relationship between various factors influencing the market price of stocks. Similar studies in Nepal have been limited to banking sector only. However, this paper aims to investigate the factors that affect the market share prices of life insurance companies listed in Nepal Stock Exchange (NEPSE). All the life insurance companies listed in Nepal Stock Exchange with panel data for the period 2012/13-2017/18 was taken as a sample for the study. The data was analyzed through descriptive and inferential statistics, while the hypothesis was tested using the regression coefficients based on the results of the multiple regression model in this study. The study revealed that earning per share, dividend per share, price-earnings ratio, age of the company and dividend yield are the major determinants of share price. The study concludes that dividends play a major role when Nepalese investors make investment. Further, it was revealed that dividend policy of the companies plays a major role in shaping investor decisions in Nepal.